Case Report on Pre-Marital Screening, Information Communication, and Reproductive Health Education for Prospective Brides - Shohipatul Mawaddah; Ziadatul Munawarah; Nurul Aulia Kamila; Rosa Mutianingsih; Siti Mardianingsih (Indonesian Journal of Global Health Research, 2024)
Premarital screening is one of the government's program strategies for all prospective brides and grooms to find out the risks that will be faced by the couple, and also for their children in the future. Many things can be anticipated by conducting this screening, such as the risk of disease transmission, infertility, maternal and child mortality during childbirth, and birth defects. The purpose of this case study is to conduct premarital screening and assistance in the form of providing health reproductive (communication, information, education). A pair of prospective brides and grooms (calon pengantin) planning to get married in 1 month visit the Health Center for a premarital examination. As per the Health Center's work procedure, they undergo a premarital screening examination and receive follow-up. The results of anamnesis and physical examination of both candidates were normal, laboratory examination results showed that only the bride to be's hemoglobin levels was below normal (10.8 gr/dL). Assistance was provided to both brides and grooms 3 times, 1 time at the Health Center and 2 home visits, midwifery care provided in the form of providing iron tablets and Tetanus Toxoid immunization to the bride and health reproductive (communication, information, education) to both. The final visit showed that the knowledge of both brides and grooms was in the very good category. Both prospective brides and grooms are ideal age biologically and psychologically to get married.